Research on Optimization of Parametric Propeller Based on Anti-Icing Performance and Simulation of Cutting State of Ice Propeller - Yu Lu; Chunxiao Wu; Shewen Liu; Zhuhao Gu; Wu Shao; Chuang Li (Journal of Marine Science and Engineering, 2021)
When a ship sails in an ice area, the ice could cause damage to ship hull and the propeller as well as the rudder. In the design process of an ice class propeller, the strength verification of the propeller has always been the focus of the design and research of the ice propeller. Based on the International Association of Classification Societies Unified Requirements for Polar Class (IACS Polar UR), it is required that the maximum torque from the propeller cannot exceed the required value to ensure the safety of the propeller shafting equipment. This paper investigates the hydrodynamic performance of the propeller under the condition of satisfying the propeller’s ice strength. A parametric propeller optimization design procedure was established in which the thrust coefficient and open water efficiency solved by CFD method were selected as the objective function and optimization target, the maximum ice torque was used as the optimization constraint under the condition that the ship’s shafting equipment remains unchanged, the propeller pitch, thickness, and camber at each radial direction were taken as the optimization design variables, and the optimization algorithm of SOBOL and NSGA-II was adopted. The interaction mode of propeller and ice was simulated by the method of explicit dynamics. The equivalent stress and displacement response of the blade during the cutting process of the ice propeller were calculated, monitoring the ice destruction process. The results show that the multi-objective Pareto optimal solution set of thrust coefficient and open water efficiency of the ice class propeller was formed at the design speed while maintain the maximum ice torque not exceeding the original ice torque.